2018
DOI: 10.1016/j.conengprac.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven repetitive control: Wind tunnel experiments under turbulent conditions

Abstract: A commonly applied method to reduce the cost of wind energy, is alleviating the periodic loads on turbine blades using Individual Pitch Control (IPC). In this paper, a data-driven IPC methodology called Subspace Predictive Repetitive Control (SPRC) is employed. The effectiveness of SPRC will be demonstrated on a scaled 2-bladed wind turbine. An open-jet wind tunnel with an innovative active grid is employed to generate reproducible turbulent wind conditions. A significant load reduction with limited actuator d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…At the next rotation count, the state Kj+1 will be updated and used to be an initial condition of the MPC optimization. Following the philosophy of the receding horizon principle [16], the cost function in (12) will roll ahead one step and all the procedure will be repeated.…”
Section: B Receding Horizon Repetitive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…At the next rotation count, the state Kj+1 will be updated and used to be an initial condition of the MPC optimization. Following the philosophy of the receding horizon principle [16], the cost function in (12) will roll ahead one step and all the procedure will be repeated.…”
Section: B Receding Horizon Repetitive Controlmentioning
confidence: 99%
“…This paper introduces a method called constrained Subspace Predictive Repetitive Control (SPRC) to include the physical constraints into a pitch controller for load reduction. The basic idea of SPRC was initially proposed by van Wingerden et al [9], which showed promising results in numerical study [10] and in wind tunnel experiments [11], [12]. Since it is a fully data-driven approach consisting of subspace identification [13] and repetitive control, it was also extended for adaptive fault-tolerant control [6], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of SPRC was initially proposed by van Wingerden and Hulskamp 26 . It showed promising results in simulations 27 and in wind tunnel experiments 28,29 . Moreover, preliminary results of SPRC in fault‐tolerant control have been shown in other studies 30,31 …”
Section: Introductionmentioning
confidence: 97%
“…Based on it, a predictive repetitive control law is then formulated to reduce only specific deterministic loads, such as 1P loads, under varying operating conditions. The SPRC approach has shown promising results in numerical simulations (Navalkar et al, 2014;Liu et al, 2020) and in wind tunnel experiments (Navalkar et al, 2015;Frederik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%